Mist-lining of a baroque painting - Andreja Ravnikar (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The paper presents the mist-lining method, executed on the Baroque paintingJesus among Teachers (Jezus med učeniki) from the St. Trinity Church in Ljubljana. The procedure was selected with consideration to previous research and comparison to the nap-bonding method, quantities of glue used, the weight of the added material, as well as the ease with which the lining could be removed at a later time. Both methods were tested on various linings in view of the two basic principles – minimal intervention and reversibility.